Tridente da leitura: subsídio didáctico para um ensino-aprendizagem da leitura e compreensão de enunciados escritos, caso curso de Enfermagem do Instituto Superior Privado do Waku Kungo/Polo Sumbe - Belarmino Simão Proença Justino; Adelino Joaquim Pongo Balança; Chico Chipia Canjenje; Simão Adão Mariti (Revista ft, 2026)
This study addresses the challenges associated with reading, interpreting, and comprehending written statements. Its aim is to develop didactic strategies for teaching the comprehension and interpretation of written statements in an interactive and pragmatic manner for Nursing students at the Waku Kungo Private Higher Education Institute (ISPWK). Furthermore, it reflects on the importance of positioning the text as the central object of the Portuguese language class. This topic arises from the observation that the majority of nursing students struggle to interpret and comprehend written statements; this constitutes a problem, as it prevents them from efficiently and effectively completing the tasks common to their studies and curricular assessments. The research is theoretically grounded in the work of Marcuschi (1996) and Solé (2014), specifically regarding reading from interactionist, functionalist, and cognitivist perspectives. The study employed a qualitative methodology with a descriptive approach; the corpus consisted of an analysis of a reading, interpretation, and text comprehension lesson within the Portuguese Language course for first-year Nursing students (Class 101) during the 2025–2026 academic year. The study demonstrated that the didactic-pedagogical procedures for teaching, assessing, and learning the reading, interpretation, and comprehension of written statements must be meticulously conceived, prepared, and proficiently structured. The goal is to foster critical students capable of reading and analyzing statements or texts in a coherent, assertive, and contextualized manner—aligned with the author's intended message—thereby creating harmony within the author-text-reader triad.